Compassion fatigue and satisfaction: A cross‐sectional survey among US healthcare workers. (13th May 2013) - Smart, Denise; English, Ashley; James, Jennifer; Wilson, Marian; Daratha, Kenn B.; Childers, Belinda; Magera, Chris
Abstract Professional quality of life among healthcare providers can impact the quality and safety of patient care. The purpose of this research was to investigate compassion satisfaction and compassion fatigue levels as measured by the Professional Quality of Life Scale self‐report instrument in a community hospital in the United States. A cross‐sectional survey study examined differences among 139 RNs, physicians, and nursing assistants. Relationships among individual and organizational variables were explored. Caregivers for critical patients scored significantly lower on the Professional Quality of Life subscale of burnout when compared with those working in a noncritical care unit. Linear regression results indicate that high sleep levels and employment in critical care areas are associated with less burnout. Identification of predictors can be used to design interventions that address modifiable risks.